Astrocyte‐derived lipocalin‐2 mediates hippocampal damage and cognitive deficits in experimental models of vascular dementia - Kim, Jae‐Hong; Ko, Pan‐Woo; Lee, Ho‐Won; Jeong, Ji‐Young; Lee, Maan‐Gee; Kim, Jong‐Heon; Lee, Won‐Ha; Yu, Ri; Oh, Won‐Jong; Suk, Kyoungho (Glia, 2017)
Lipocalin‐2 (LCN2) has diverse functions in multiple pathophysiological conditions; however, its pathogenic role in vascular dementia (VaD) is unknown. Here, we investigated the role of LCN2 in VaD using rodent models of global cerebral ischemia and hypoperfusion with cognitive impairment and neuroinflammation. Mice subjected to transient bilateral common carotid artery occlusion (tBCCAo) for 50 min showed neuronal death and gliosis in the hippocampus at 7 days post‐tBCCAo. LCN2 expression was observed predominantly in the hippocampal astrocytes, whereas its receptor was mainly detected in neurons, microglia, and astrocytes. Furthermore, Lcn2‐deficient mice, compared with wild‐type animals, showed significantly weaker CA1 neuronal loss, cognitive decline, white matter damage, blood–brain barrier permeability, glial activation, and proinflammatory cytokine production in the hippocampus after tBCCAo. Lcn2 deficiency also attenuated hippocampal neuronal death and cognitive decline at 30 days after unilateral common carotid artery occlusion (UCCAo). Furthermore, intracerebroventricular (i.c.v) injection of recombinant LCN2 protein elicited CA1‐neuronal death and a cognitive deficit. Our studies using cultured glia and hippocampal neurons supported the decisive role of LCN2 in hippocampal neurotoxicity and microglial activation, and the role of the HIF‐1α–LCN2–VEGFA axis of astrocytes in vascular injury. Additionally, plasma levels of LCN2 were significantly higher in patients with VaD than in the healthy control subjects. These results indicate that hippocampal damage and cognitive impairment are mediated by LCN2 secreted from reactive astrocytes in VaD. Main Points Astrocyte‐derived LCN2 mediates hippocampal damage in rodent models of vascular dementia, with higher plasma levels of LCN2 protein in patients with vascular dementia, suggesting the possibility of effective glia‐based treatment for vascular dementia.